2010
DOI: 10.1002/crat.200900704
|View full text |Cite
|
Sign up to set email alerts
|

Some structural considerations on the perovskite‐type A1‐ySryCo1‐xFexO3‐δ solid solution series

Abstract: Solid solution series of La1‐ySryCo1‐xFexO3‐δ were extensively studied in the past as cathode materials for solid oxide fuel cells. However, the crystal structure behavior of La1‐ySryCo1‐xFexO3‐δ solid solution series when La‐ions are replaced with another rare‐earth ion or metallic alkaline earth metal is at present not fully understood. Here we report X‐ray powder diffraction measurements performed on samples of the Sm0.8Sr0.2Co1‐xFexO3‐δ solid solution series. This study demonstrates that the average A‐cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The results could be correlated to the high oxygen non-stoichiometry [1], high ionic conductivity [38], as well as with the lattice expansion (volume effect) of the crystalline structure [39] reported for these compositions. For the BSCF 5582 it has been reported that about 60% of the Co 3+ ions are oxidized to Co 4+ (r Co 4þ ¼ 0:67 Å), while, at the same time, all the Fe 3+ ions are into high valence state (Fe 4+ with r Fe 4þ ¼ 0:73 Å), thus this effect has to be compensated by oxygen vacancy formation [40,41]. Increasing iron content in the heat-treated samples at 1173 K and 1223 K, the decrease of the non-stoichiometry and of the total electrical conductivity is expected [1,40].…”
Section: B-site Effect: Co/fe Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results could be correlated to the high oxygen non-stoichiometry [1], high ionic conductivity [38], as well as with the lattice expansion (volume effect) of the crystalline structure [39] reported for these compositions. For the BSCF 5582 it has been reported that about 60% of the Co 3+ ions are oxidized to Co 4+ (r Co 4þ ¼ 0:67 Å), while, at the same time, all the Fe 3+ ions are into high valence state (Fe 4+ with r Fe 4þ ¼ 0:73 Å), thus this effect has to be compensated by oxygen vacancy formation [40,41]. Increasing iron content in the heat-treated samples at 1173 K and 1223 K, the decrease of the non-stoichiometry and of the total electrical conductivity is expected [1,40].…”
Section: B-site Effect: Co/fe Variationmentioning
confidence: 99%
“…For the BSCF 5582 it has been reported that about 60% of the Co 3+ ions are oxidized to Co 4+ (r Co 4þ ¼ 0:67 Å), while, at the same time, all the Fe 3+ ions are into high valence state (Fe 4+ with r Fe 4þ ¼ 0:73 Å), thus this effect has to be compensated by oxygen vacancy formation [40,41]. Increasing iron content in the heat-treated samples at 1173 K and 1223 K, the decrease of the non-stoichiometry and of the total electrical conductivity is expected [1,40]. This effect was also evidenced for various substituted ABO 3 perovskites solid solution series (e.g.…”
Section: B-site Effect: Co/fe Variationmentioning
confidence: 99%